2015
DOI: 10.1007/s12079-015-0291-9
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence and autophagy of myoepithelial cells are involved in the progression of in situ areas of carcinoma ex-pleomorphic adenoma to invasive carcinoma. An in vitro model

Abstract: During tumor invasion, benign myoepithelial cells of carcinoma ex-pleomorphic adenoma (CXPA) surround malignant epithelial cells and disappear. The mechanisms involved in the death and disappearance of these myoepithelial cells were investigated via analysis of the expression of regulatory proteins for apoptosis, autophagy and cellular senescence in an in situ in vitro model. Protein expression relating to apoptosis (Bax, Bcl-2, Survivin), autophagy (Beclin-1, LC3B) and cellular senescence (p21, p16) was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…These findings corroborate a previous study by Silva et al, 4 who demonstrated that Myo cell disappearance from areas of invasive carcinoma in situ was not associated with apoptosis but with an induction of senescence and autophagy when Myo cells were co‐cultured with malignant epithelial cells. This could explain the loss observed in Myo cell population during the progression of ex‐pleomorphic adenoma carcinoma 5,6 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings corroborate a previous study by Silva et al, 4 who demonstrated that Myo cell disappearance from areas of invasive carcinoma in situ was not associated with apoptosis but with an induction of senescence and autophagy when Myo cells were co‐cultured with malignant epithelial cells. This could explain the loss observed in Myo cell population during the progression of ex‐pleomorphic adenoma carcinoma 5,6 .…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that MV produced by malignant epithelial cells may play an important role in the transition from in situ to invasive carcinoma in cases of carcinomas ex‐pleomorphic adenoma (CXAP). During the progression of this neoplasia, Myo cells disappear, 5,6 and recent evidence has suggested that these cells may undergo autophagy‐senescence 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for cnidarian epitheliomuscular cells, bilaterians myoepithelial cells originate from tissues of various developmental origins (Petersen and van Deurs, 1989; Schmidt-Rhaesa, 2007; Tamgadge et al, 2013). Furthermore, myoepithelial cells in mammalians are receiving increasing interest, because of their importance in processes such as gland development, growth and differentiation, in pathologies such as breast cancer (Silva et al, 2015) as well as their capacity to control tumorigenesis (Gudjonsson et al, 2005; reviewed in Deugnier et al, 2002; Sopel, 2010). Thus, it could be particularly fruitful to compare bilaterian myoepithelial and cnidarian epitheliomuscular cells, their developmental origin, the molecular or mechanical signals that control their polarization, condensation and organization into muscle nets, rings or fibers and how they regenerate after injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, this condition is short-lived, as myoepithelial cells rapidly disappear (8,9). A number of hydrolytic enzymes, released either by the tumor cells or by cells surrounding the tumor, combined with certain growth factors may favor disruption of the basement membrane, contributing to EMT (10).…”
Section: Introductionmentioning
confidence: 99%